ROLE OF SOCİAL COOPERATİVES İN IMPLEMENTİNG SOCİAL POLİCİES OF LOCAL GOVERNMENTS: HOMELESS COOPERATİVE (Third Sector Social Economic Review, 2021)
The subject of this study is handle of local governments’ view to homeless cooperative. The study is important because it filling the gap in the literature and offers a new suggestion for policymakers. It is aimed to open discussion about homeless cooperative in relation to local governments which has a duty of social services for citizens living on streets in Turkey with investigating example of Slovenia. The homeless cooperative named Zadruga Stara Roba Nova Raba and its relation to local governments are the scope of the study. In this context, qualitative research method, case study, and semi-structured interview research techniques are used. It is suggested that in Turkey homelessness ought to be taken as a problem at national and local context and established homeless cooperative supported by local government in line with their duty of social services.
Keywords: Cooperative; homeless cooperative; local governments; social cooperative; social policy.